STRATEGI MITIGASI BANJIR BERDASARKAN KAPASITAS SALURAN DRAINASE DI KELURAHAN JAGALAN - Palawa’ae, Elang Rahma; Hadiani, Rintis; Muttaqien, Adi Yusuf (Prodi Teknik Sipil Fakultas Teknik Universitas Sebelas Maret Surakarta, 2024)
Flood mitigation is an important step in maintaining the sustainability and safety of urban environments. One key factor that affects the capacity of drainage channels is the flow rate of water through the channels. Therefore, this research aims to assess flood mitigation strategies based on the flow rate in drainage channels using the HSS SCS method. The study was conducted in Jagalan Sub-District, which frequently experiences flooding due to inadequate drainage channel capacity. The HSS SCS method was used to estimate the maximum flow rate that can be accommodated by the drainage channels. Hydrological and topographic data of the study area were collected and analyzed to identify relevant hydrological characteristics and physical parameters.The analysis results showed the planned flood discharge values in Jagalan Sub-District through the Kali Boro Watershed, which were 3.1154 mm3/dt for a 2-year return period, 3.8297 mm3/dt for a 5-year return period, 4.3025 mm3/dt for a 10-year return period, and 4.7501 mm3/dt for a 20-year return period. The existing discharge values were 14.5243 mm3/dt for Surya Road, 19.1823 mm3/dt for Rejosari Road, 8.7376 mm3/dt for Kali Kepunton Road, 66.0338 mm3/dt for Kali Simpang Road, 21.7882 mm3/dt for Bororejo Road, and 42.2077 mm3/dt for Ir. Juanda Road. From these values, it can be concluded that the drainage channels in Jagalan Sub-District have sufficient capacity to accommodate the maximum flow rate during high-intensity rainfall.